2017
DOI: 10.1165/rcmb.2017-0019oc
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Regulatory T Cell Expression of Keratinocyte Growth Factor Enhances Lung Epithelial Proliferation

Abstract: Repair of the lung epithelium after injury is a critical component for resolution; however, the processes necessary to drive epithelial resolution are not clearly defined. Published data demonstrate that Foxp3 regulatory T cells (Tregs) enhance alveolar epithelial proliferation after injury, and Tregs in vitro directly promote type II alveolar epithelial cell (AT2) proliferation, in part by a contact-independent mechanism. Therefore, we sought to determine the contribution of Treg-specific expression of a grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 52 publications
1
94
0
Order By: Relevance
“…It has been reported that KGF expression on Tregs can be induced by LPS, which suggests that Tregs have the ability to express KGF under stimulated conditions [64]. Lung Tregs express higher levels of KGF than those from the spleen, which could be stimulated by TCR stimulation, and they failed to further augment expression by addition of IL-18 or IL-33 [65].…”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that KGF expression on Tregs can be induced by LPS, which suggests that Tregs have the ability to express KGF under stimulated conditions [64]. Lung Tregs express higher levels of KGF than those from the spleen, which could be stimulated by TCR stimulation, and they failed to further augment expression by addition of IL-18 or IL-33 [65].…”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%
“…Lung Tregs express higher levels of KGF than those from the spleen, which could be stimulated by TCR stimulation, and they failed to further augment expression by addition of IL-18 or IL-33 [65]. In addition, Treg can be regulated by KGF.…”
Section: Functional Molecules Expressed or Produced By ‘Repair’ Tregsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung tissue was processed to form a single cell suspension and immunostained to identify cell types as previously described (Dial et al. ). Antibodies were obtained from Biolegend (San Diego, CA): CD45 FITC (clone 30‐F11), SiglecF PE (clone E50‐2440), Annexin V PerCP‐Cy5.5 (catalog 640936), CD64 PE‐Cy7 (clone X54‐5/7.1), Ly6G APC (clone 1A8), CD3 FITC (clone 145‐2C11), CD45 Alexa Fluor 700 (clone 30‐F11), CD4 PB (clone GK1.5), Foxp3 Alexa Fluor 647 (clone 150D), Zombie Aqua™ (catalog 423102); from BD Horizon (Waltham, MA): Ly6C BV421 (clone AL‐21); and from BD Pharmingen (Waltham, MA): CD16/CD32 Mouse BD Fc block™ (clone 2.462).…”
Section: Methodsmentioning
confidence: 99%